D‐Allulose Supplementation Prevents Diet‐Induced Hepatic Lipid Accumulation via miR‐130‐Mediated Regulation in C57BL/6 Mice. Issue 3 (16th December 2022) - Yamazaki, Mirai; Okito, Misaki; Harada, Akio; Miyake, Keisuke; Tamiya, Takashi; Nakamura, Takehiro
Abstract : Scope: d ‐allulose is a low‐calorie rare sugar. It has been reported that d ‐allulose supplementation significantly inhibits diet‐induced hepatic fat accumulation. However, the underlying molecular mechanisms remain unclear. This study elucidates the mechanism underlying the suppressive effect of d ‐allulose on hepatic fat accumulation in terms of miRNA regulation. Methods and results: Male C57BL/6 mice are divided into three experimental groups–normal diet and distilled water (CC group), high‐fat diet (HFD) and distilled water (HC group), and HFD and 5% d ‐allulose solution (HA group)–and fed the respective diets for 8 weeks. Weight gain is significantly lower in the HA group than that in the HC group, although the caloric intake is the same in both. Histological analysis of liver tissues reveals excessive lipid accumulation in the HC group; this is greatly attenuated in the HA group. Real‐time PCR and western blot analyses demonstrate that, compared to the HC group, the HA group exhibits decreased hepatic PPARγ and CD36 expression. Hepatic miR‐130 expression levels are higher in the HA group than those in the CC and HC groups. Conclusions: These results indicate that miRNA changes associated with PPARγ may underlie the suppression of hepatic lipid accumulation induced by d ‐allulose intake. Abstract : d ‐allulose intake upregulates hepatic miR‐130 expression, thereby leading to the decreased expression of hepatic peroxisome proliferator‐activated receptor‐γ ( Pparg ) mRNA, which in turn suppresses cluster of differentiation 36 ( Cd36 ) expression. It is suggested that the suppression of hepatic lipid accumulation induced by d ‐allulose intake is associated with increased hepatic miR‐130 expression.